Aktualisasi Nilai-Nilai Pancasila dalam Undang-Undang Wakaf - Sadzali, Ahmad; Pratiwi, Dian Kus; Saifudin (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2022)
Law Number 41 of 2004 concerning Waqf is one of the reform products that have received the attention of many researchers. This paper examined the Waqf Law from the perspective of Pancasila, namely to answer whether the values of Pancasila have been actualized in it. This research is a juridical-normative study, by analyzing the contents of Waqf Law with the parameters of Pancasila values in the legislation. The results show that the values of Pancasila are well actualized in Waqf Law. The actualization of Pancasila values is contained in in every norm of Waqf Law.